Constraints on Higgs boson properties using WW∗(→eνμν)jj production in 36.1fb−1 of s√=13 TeV pp collisions with the ATLAS detector - Aad, G.; Abbott, B.; Abbott, D. C.; Aliev, M.; Didenko, M.; Kostyukhin, Vadim V.; Kuchinskaya, Olesya I. (The European Physical Journal C)
This article presents the results of two studies of Higgs boson properties using the WW*(-> e nu mu nu)jj final state, based on a dataset corresponding to 36.1fb(-1) of root s = 13 TeV proton-proton collisions recorded by the ATLAS experiment at the Large Hadron Collider. The first study targets Higgs boson production via gluon-gluon fusion and constrains the CP properties of the effective Higgs-gluon interaction. Using angular distributions and the overall rate, a value of tan (alpha) = 0.0 +/- 0.4(stat.) +/- 0.3(syst.) is obtained for the tangent of the mixing angle for CP-even and CP-odd contributions. The second study exploits the vector-boson fusion production mechanism to probe the Higgs boson couplings to longitudinally and transversely polarised W and Z bosons in both the production and the decay of the Higgs boson; these couplings have not been directly constrained previously. The polarisation-dependent coupling-strength scale factors are defined as the ratios of the measured polarisation-dependent coupling strengths to those predicted by the Standard Model, and are determined using rate and kinematic information to be a(L) = 0.91(-0.18)(+0.10)(stat.)(-0.17)(+0.09)(syst.) and a(T) = 1.2 +/- 0.4(stat.)(-0.3)(+0.2)(syst.). These coupling strengths are translated into pseudo-observables, resulting in kappa(VV) = 0.91(-0.18)(+0.10)(stat.)(-0.17)(+0.09)(syst.) and epsilon(VV) = 0.13(-0.20)(+0.28)(stat.)(-0.10)(+0.08)(syst.). All results are consistent with the Standard Model predictions.